7.8 ARTERIAL STIFFNESS AND SYSTEMIC INFLAMMATION IN COPD PATIENTS - Renata Marietta Bocskei; Lilla Tamasi; Bela Benczur; Attila Cziraki; Gyorgy Losonczy; Aniko Bohacs (Artery Research, 2016)
Background: COPD is one of the leading causes of mortality worldwide. Systemic low-grade inflammation is a common finding in COPD. Soluble urokinase-type plasminogen activator receptor (suPAR) indicates an inflammatory state and it has an association with atherosclerosis and cardiovascular disease (CVD). ThesuPAR reflects different aspects of inflammation as high sensitive C-reactive protein (hsCRP) and IL-6. Elevated CVD risk is observed in COPD. However the correlation between COPD and arterial stiffness is rarely investigated in the literature. We investigated the association between some inflammatory biomarkers (suPAR, IL-6, hsCRP) and arterial stiffness in COPD and control patients. Methods: We measured 45 middle aged individuals (25 COPD and 20 control normotensive patients) without diabetes and cardiovascular disease. IL-6, hsCRP, suPAR were determined in fasting blood samples. Whole body plethysmography, assessment tests and aortic pulse wave velocity (aoPWV), augmentation index (Aix), central systolic blood pressure (cSBP) were determined. COPD patients were categorized according to GOLD-classification. Results: Patients with COPD have a higher level of IL-6 (5.38 vs 3.63 pg/ml p=0.022), suPAR (2.84 vs 2.41 ng/ml p=0.036), and hsCRP (2.99 vs 1.91 mg/L p=0.068). The patients with COPD have a significant higher aoPWV (p=0.002), and cSBP (p=0.022). Conclusion: In this study we found elevated inflammatory markers and aoPWV in COPD patients, both of them indicate the presence of earlier atherosclerosis than in controls without COPD.